Constraints of Pamong Praja Police in Law Enforcement of Food Traders - Tri Lestari Hadiati; Darmawan Tri Budi Utomo; Dian Adi Saputra (LEGAL BRIEF, 2022)
Local governments seek to enforce regional regulations and have a role as law enforcement officers through the Civil Service Police Unit (Satpol PP). This is contained in Government Regulation (PP) Number 16 of 2018 concerning the Civil Service Police Unit. The regional government of Blora Regency through the Civil Service Police Unit of Cepu Subdistrict is also optimizing efforts to enforce Regional Regulations (Perda). So far, in practice in the field, many violations are found on the shoulder of the road and the sidewalk is not functioning at several points in Cepu District, as stated in Regional Regulation 01 of 2017 concerning Public Order. The purpose of this study is to analyze the constraints and find solutions to the role of Satpol PP in Cepu District, Blora Regency in law enforcement against Street Vendors (PKL) who sell on the sidewalks of the Cepu PLN office. This type of research is normative juridical. The results of this study 1. Law enforcement of street vendors who occupy the sidewalks of the PLN Cepu unit. The role of the Cepu District Civil Service Police Unit is to demolish the permanent stalls belonging to street vendors. This will create an orderly society against the rule of law. 2. Obstacles faced if there are street vendors who are found to be selling again on the sidewalk area of This will create an orderly society against the rule of law. 2. Obstacles faced if there are street vendors who are found to be selling again on the sidewalk area of This will create an orderly society against the rule of law. 2. Obstacles faced if there are street vendors who are found to be selling again on the sidewalk area of the PLN Cepu Unit Office, this must be immediately warned so that the number of street vendors who resell in the area does not increase. 3. The solution is to have regular discussions or socialization regarding Regional Regulation 01 of 2017 concerning public order and Regional Regulation number 20 of 2018 concerning the Arrangement and Empowerment of Street Vendors to PKL and former PKL associations.